EFFECTS OF MODERATELY VIRULENT AFRICAN SWINE FEVER VIRUS ON INTERLEUKIN-10 PRODUCTION - A. S. Pershin; I. V. Shevchenko; A. S. Igolkin; Ye. V. Aronova; N. N. Vlasova (Ветеринария сегодня)
A characteristic feature of African swine fever virus (ASFV) is the ability to escape from host immune response, affecting macrophages and replicating in them. Besides, ASFV - specific antibodies do not completely neutralize the virus. Cytokines are important factors for various viral infection pathologies. The virulence of ASFV isolates may depend on the capacity to regulate cytokine expression by macrophages. Thus, when comparing in vitro and in vivo cytokine production by macrophages, it was established that infection with low virulent virus isolates leads to an immune response with a predominance of cytokines involved in cellular immunity, such as INF-α and IL-12p40, as compared with infection with highly virulent isolates. The aim of this paper was to study the effect of African swine fever virus on the production of IL-10, a pleiotropic cytokine that inhibits synthesis of cytokines and shows a strong antiinflammatory effect. For this, 12 piglets were experimentally infected intramuscularly with a continuous cell culture-adapted ASFV isolate Vero25 at a dose of 10 HAdU per animal followed by control infection of surviving animals with the reference virus isolate Arm 07 at a dose of 1,000 HAdU per animal. Temperature measurements were taken and blood sampling to obtain serum was conducted during the experiment. IL-10 amount in blood sera was determined using Invitrogen test systems (Thermo Fisher, USA). A higher IL-10 level (15.8–173 pg/ml) was observed in blood sera of dead animals infected with a moderately virulent virus, as compared with surviving pigs (4–5 pg/ml). No correlation between the speed of appearance of specific antibodies and IL-10 serum levels has been established. No noticeable effect of the IL-10 serum level prior to infection on the survival rate of animals has been observed. Further studies are needed to establish a causal relationship, including study of the expression of various cytokines during infection with both low- and highly virulent virus isolates.